Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To find an equivalent equation that can replace [tex]\(3x + 5y = 59\)[/tex] in the given system without changing the solution, we need to consider the process of elimination and linear combinations.
The original system of equations is:
1. [tex]\(3x + 5y = 59\)[/tex]
2. [tex]\(2x - y = -4\)[/tex]
We want to transform the second equation in such a way that it can replace the first equation but will still maintain the solution. Here's how we can do it:
1. Multiply the second equation by a factor that will help eliminate one of the terms when added to or subtracted from another equation. For instance, by multiplying the second equation by 5, we get:
[tex]\[ 5 \cdot (2x - y) = 5 \cdot (-4) \][/tex]
which simplifies to:
[tex]\[ 10x - 5y = -20 \][/tex]
2. Now we look at our original first equation:
[tex]\[ 3x + 5y = 59 \][/tex]
3. We can now consider adding these two equations together to see if we can eliminate the [tex]\(y\)[/tex] term:
[tex]\[ 3x + 5y = 59 \\ 10x - 5y = -20 \][/tex]
Adding these equations:
[tex]\[ (3x + 10x) + (5y - 5y) = 59 + (-20) \][/tex]
simplifies to:
[tex]\[ 13x = 39 \][/tex]
Thus, adding these modified equations results in the simplified equation:
[tex]\[ 13x = 39 \][/tex]
Therefore, the equivalent equation that can replace [tex]\(3x + 5y = 59\)[/tex] without changing the solution is:
[tex]\[ \boxed{13x = 39} \][/tex]
The original system of equations is:
1. [tex]\(3x + 5y = 59\)[/tex]
2. [tex]\(2x - y = -4\)[/tex]
We want to transform the second equation in such a way that it can replace the first equation but will still maintain the solution. Here's how we can do it:
1. Multiply the second equation by a factor that will help eliminate one of the terms when added to or subtracted from another equation. For instance, by multiplying the second equation by 5, we get:
[tex]\[ 5 \cdot (2x - y) = 5 \cdot (-4) \][/tex]
which simplifies to:
[tex]\[ 10x - 5y = -20 \][/tex]
2. Now we look at our original first equation:
[tex]\[ 3x + 5y = 59 \][/tex]
3. We can now consider adding these two equations together to see if we can eliminate the [tex]\(y\)[/tex] term:
[tex]\[ 3x + 5y = 59 \\ 10x - 5y = -20 \][/tex]
Adding these equations:
[tex]\[ (3x + 10x) + (5y - 5y) = 59 + (-20) \][/tex]
simplifies to:
[tex]\[ 13x = 39 \][/tex]
Thus, adding these modified equations results in the simplified equation:
[tex]\[ 13x = 39 \][/tex]
Therefore, the equivalent equation that can replace [tex]\(3x + 5y = 59\)[/tex] without changing the solution is:
[tex]\[ \boxed{13x = 39} \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.